Valorization of date palm sap into commercially viable products: a comprehensive account on its composition, nutritional profile, processing, value addition, and potential applications - Roobab, Ume; Naqash, Farah; Kurup, Shyam; Maqsood, Sajid (Frontiers in Sustainable Food Systems, 2025)
Date palm sap, obtained as an exudate from date palms, is a nutritionally rich substance with significant potential as a functional food ingredient and natural sweetener. Despite the growing interest in the nutritional, economic, and cultural significance of date palm sap, research on its comprehensive benefits and risks remains limited. This review aims to summarize the current knowledge on the physicochemical properties, microbiological composition, nutritional value, traditional uses, and health risks associated with date palm sap consumption. Sap composition, influenced by factors such as tapping period and palm variety, includes high levels of sugar, minerals, vitamins, amino acids, and bioactive compounds. It harbors a diverse microbial community that affects quality and fermentation outcomes. Traditional uses include fresh consumption, fermented beverages, and sugar production, which are of socioeconomic importance in several regions. However, raw sap consumption poses health risks, particularly involving Nipah virus transmission. Innovative approaches for processing and preservation are being explored to extend the shelf life while maintaining nutritional quality. The sap also shows promise as a feedstock for bio-based products. This review highlights research gaps and future directions, including the optimization of processing techniques, characterization of sap composition across cultivars, evaluation of long-term health effects, development of risk communication strategies, and exploration of novel applications. A multidisciplinary approach that integrates traditional knowledge with modern scientific methods is crucial for realizing the full potential of date palm sap, addressing safety concerns, and ensuring sustainable production.